AB0545 Is lupus more prevalent in world's most stressed countries?. (12th June 2018) - Almathkouri, A.; Pyne, D.; Pakozdi, A.; Rajkariar, R.; Cove-smith, A.; Lewis, M.; ,
Abstract : Background: A number of studies have implicated psychological stress as a trigger for autoimmune diseases. In a questionnaire study involving 120 lupus patients emotional stress was selected in over 75% cases as a trigger for their disease 1 . The role of stress as a trigger in lupus however is controversial. Here we study whether there is an association between the prevalence of lupus in various countries and their reported stress measures. Methods: We undertook a literature review of the reported prevalence of lupus in various countries across the world. We then recorded the reported stress index in those countries from Bloomberg's study 2, which utilised seven equally weighted variables: homicide rates, GDP per capita income inequality, corruption perception, unemployment, urban air pollution and life expectancy to rank 74 countries according to stress levels. Pearsons correlation was used to measure association between national stress indices and lupus prevalence Results: Results are presented in graph 1. Prevalence data was only available in the literature for limited countries. Of the countries studied no correlation was found between national stress indices and lupus prevalence (r=−0.028 (p-value 0.449) Conclusions: We found no association between a country's prevalence of lupus and the measured stressfulness of its living environment. References: [1] Stojanovich L. Stress as a trigger of autoimmune disease. Abstracts book: 5th International Congress on Autoimmunity, Sorrento, Italy, vol. 355. Autoimmun Rev; 2006. [2] United Nations Office on Drugs and Crime, International Monetary Fund, Central Intelligence Agency World Factbook, Transparency International, World Health Organization. May 2013. Disclosure of Interest: None declared